A study on factors that affecting on employees’ job satisfaction among supporting units staff at Malaysia Marine and Heavy Engineering Sdn Bhd (MMHE) / Lina Marliana Mohamed Noor - Mohamed Noor, Lina Marliana (Faculty of Business and Management, 2010)
The concept of job satisfaction is defined as an individual’s attitude about work roles and the relationship to worker motivation. There could be no job satisfaction where there is no motivation. As we noticed, anytime and every organization in this world, the main thing that they should take into account is employees’ job satisfaction. Without having this, the whole organization might collapse as it always rely and depends on employees. Therefore, in any ways, the leader or the management should highlight on how to satisfy their employees. This is very necessary to make sure the employees can stay longer and keep loyal towards the organization. Hence, this research aims to investigate and identify the Job Satisfaction Factors among supporting units staff at Malaysia Marine and Heavy Engineering (MMHE) Sdn Bhd. At the end, this research will determine whether Job Satisfaction Factors such as Leadership Style, Organizational Culture, Organizational Learning and Job Characteristics will affect towards Employees’ Job Satisfaction at MMHE or not. By using all of the 60 Questionnaires, the findings highlighted on the four Job Satisfaction Factors as mentioned. Therefore, in order to determine the relationship between Job Satisfaction Factors and Employees’ Job Satisfaction, a Likert-type scale has been developed and tested. Therefore in this research, the researcher tries to identify the most influential factor and the relationship between dependent and independent variables.